A Maverick-like cluster in the genome of a pathogenic, moderately virulent strain of Gallibacterium anatis, ESV200, a transient biofilm producer - Patricia Sanchez-Alonso; Elena Cobos-Justo; Miguel Angel Avalos-Rangel; Lucía López-Reyes; Gloria Luz Paniagua-Contreras; Felipe Vaca-Paniagua; Felipe Vaca-Paniagua; Estela Anastacio-Marcelino; Ana Jaqueline López-Ochoa; Victor M. Pérez Marquez; Erasmo Negrete-Abascal; Candelario Vázquez-Cruz (Frontiers in Microbiology, 2023)
IntroductionGallibacterium anatis causes gallibacteriosis in birds. These bacteria produce biofilms and secrete several fimbrial appendages as tools to cause disease in animals. G. anatis strains contain up to three types of fimbriae. Complete genome sequencing is the strategy currently used to determine variations in the gene content of G. anatis, although today only the completely circularized genome of G. anatis UMN179 is available.MethodsThe appearance of growth of various strains of G. anatis in liquid culture medium was studied. Biofilm production and how the amount of biofilm was affected by DNase, Proteinase K, and Pronase E enzymes were analyzed. Fimbrial gene expression was performed by protein analysis and qRT-PCR. In an avian model, the pathogenesis generated by the strains G. anatis ESV200 and 12656-12 was investigated. Using bioinformatic tools, the complete genome of G. anatis ESV200 was comparatively studied to search for virulence factors that would help explain the pathogenic behavior of this strain.Results and DiscussionG. anatis ESV200 strain differs from the 12656-12 strain because it produces a biofilm at 20%. G. anatis ESV200 strain express fimbrial genes and produces biofilm but with a different structure than that observed for strain 12656-12. ESV200 and 12656-12 strains are pathogenic for chickens, although the latter is the most virulent. Here, we show that the complete genome of the ESV200 strain is similar to that of the UNM179 strain. However, these strains have evolved with many structural rearrangements; the most striking chromosomal arrangement is a Maverick-like element present in the ESV200 strain.